The Glycemic Index of Gayam (Inocarpus fagifer Forst) Cookies as a High Dietary Fiber Food - Wijanarka, Agus; Tifauzah, Noor; Khasanah, Furaida; Nirmala Dewi, Anisah; Setyaningsih, Lilis (JURNAL INFO KESEHATAN, 2024)
The type 2 diabetes (T2D) is still one of the world's public health problems. It needs serious handling and prevention efforts in the nutritional aspect. The high prevalence of T2D is related to the low intake of dietary fiber. This type of food has a low glycemic index (GI). Gayam is a high-dietary fiber material that can be used for the manufacture of flour and as processed food material for the high-dietary fiber cookies. The objectives of this research were to study the GI evaluation of cookies from gayam flour. Cookies were tested for chemical composition, and glycemic index. The glycemic index evaluation test used 12 volunteers taken from the healthy group/nondiabetic, normal nutritional status (BMI: 18.5-22.9), and age 19-55 years. The results of this study indicate the dietary fiber content of gayam cookies was 4.57 g/100 g and included in the category of high dietary fiber food. The glycemic index of gayam cookies was 43 and the low glycemic index category. The obtained results show for the first time the potential of gayam cookies in hyperglycaemia management. The conclusion of this study was that gayam cookies has high dietary fiber content and low GI level. Gayam cookies can be used as an alternative snack to control blood glucose levels in the prevention of diabetes mellitus.